1999
DOI: 10.2134/jeq1999.00472425002800010038x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Selenium Volatilization: Method of Measurement under Field Conditions

Abstract: An open‐flow chamber sampling system was developed for measurements of selenium (Se) volatilization from soil and vegetated areas under field conditions. This paper provides detailed information on the design, construction, and calibration of the chamber sampling system. Volatile Se was collected using a Plexiglas collection chamber, 0.71 m long, 0.71 m wide, and 0.76 in high; the chamber provided an internal volume of 0.38 m3 and enclosed a ground area of 0.5 m2. Volatile Se produced inside the collection cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The amount of Se volatilized by different crops in Se‐contaminated fields at the second experimental site was measured by following the technique of Lin et al. (1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of Se volatilized by different crops in Se‐contaminated fields at the second experimental site was measured by following the technique of Lin et al. (1999).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of Se volatilized by different crops in Se-contaminated fields at the second experimental site was measured by following the technique of Lin et al (1999). Volatile Se was collected using Plexiglass collection chambers of 0.70 m length, 0.70 m width and 1.20 m height with inlet and outlet openings at the top.…”
Section: In Situ Se Volatilization From Standing Cropsmentioning
confidence: 99%
“…Volatile Se was collected with an open‐flow sampling chamber system (Lin et al, 1999). The dimensions of the Plexiglas collection chamber were 0.71 m long, 0.71 m wide and 0.76 m high; the chamber provided an internal volume of 0.38 m 3 and enclosed a bottom area of 0.5 m 2 The sampling chamber was fitted to the top of each microcosm.…”
Section: Methodsmentioning
confidence: 99%
“…Although some of the assumptions associated with these methods may not be entirely valid under real‐world situations, chambers have been used extensively for measuring emissions of a variety of gases due to their simplicity and ease in fabrication and operation. The variety of gases measured includes trace gases, such as CO 2 , N 2 O, NO x , CH 4 , and selenium (Se) (de Mello and Hines, 1994; Fukui and Doskey, 1996; Hutchinson and Mosier, 1981; Jury et al, 1982; Kanemasu et al, 1974; Valente et al, 1995; Lin et al, 1999; Dungan et al, 2000) and volatile organic compounds (VOCs), such as volatile pesticides (Gao et al, 1997; Gao and Yates, 1998a; Sanders et al, 1985; Yates et al, 1997; Yagi et al, 1993; Wang et al, 1997; Woodrow and Seiber, 1991), spilled volatile solvents, and volatile constituents from waste disposal sites (Balfour et al, 1987; Eklund, 1992). Experience gained from numerous applications of both types of flux chambers has shown that both methods have their own advantages and disadvantages.…”
mentioning
confidence: 99%